Advance selling with part payment for new to-be-released products. (14th August 2017) - Tang, Wangmei; Ang, Sheng
Abstract : Purpose: The paper aims to study a strategy of advance selling with part payment (ADP) in which pre-ordering consumers are required to pay a portion of advance price first and then pay the rest in the spot period to complete the order. The authors compare the ADP strategy with strategies of advance selling with full payment (ADF) and no advance selling (NA) from the perspective of sellers. Design/methodology/approach: The paper proposes a two-period pricing model with price-off promotion in the first period for a market consisting of consumers and a single seller. For each strategy (i.e. NA, ADF and ADP), solutions to the seller's optimal order quantity in the spot period, optimal advance price and prepayment in the advance period are derived by backward conduction. Numerical study is also used to obtain straightforward insights. Findings: Advance price of ADF is lower than that of ADP. Order quantity of ADF is higher than that of ADP. ADP brings more profit than the other two selling strategies, i.e. NA and ADF, when ADP's implementing conditions are satisfied. While ADF is effective only when unit cost is low, ADP is applicable irrespective of whether the cost is low. Originality/value: Existing researchers on advance selling mainly focus on the ADF strategy. The paper pays attention to different payment mechanisms in advance selling and steps further to propose a new form of advance selling, i.e. the ADP strategy. The effects of ADP on consumer's purchasing behavior and seller's marketing decisions are analyzed.